Women entrepreneurship in the era of digital transformation - Harshitha, S; Bhavyashree, B M; Laxmi, M; Malhotra, Naina (The International tax journal, 2026)
Women entrepreneurship has become an important driver of economic growth, innovation, employment generation, and social empowerment in the modern digital economy. The rapid advancement of digital technologies such as e-commerce, artificial intelligence, fintech, cloud computing, social media, and digital marketing has significantly transformed entrepreneurial ecosystems and created new opportunities for women entrepreneurs. Digital transformation has enabled women to overcome traditional barriers related to finance, mobility, market accessibility, and communication by facilitating online business operations and flexible work environments. The present study examines the role of digital transformation in promoting women entrepreneurship and identifies the opportunities and challenges associated with digital business environments. The study also evaluates the impact of digital entrepreneurship on women empowerment and economic development while suggesting suitable strategies and policy measures for strengthening women-led enterprises. The research adopts a descriptive and analytical methodology based on secondary data collected from journals, books, conference proceedings, government reports, online databases, and published studies from 2010 to 2026. The findings reveal that digital technologies significantly contribute to financial inclusion, business innovation, market expansion, employment generation, and entrepreneurial sustainability among women entrepreneurs.